Submission of method statement for anti-termite treatment work over the plinth filling as per BOQ Item No. 4.4 - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the submission of method statement for anti-termite treatment work over the plinth filling as per BOQ Item No. 4.4 of BRAC University new campus project.